Interpreting, translating or investigating? Framing the competences of a hybrid translational field: intercept interpreting. - Griebel, Cornelia; Havelka, Ivana (Perspectives: Studies in Translatology, 2025)
When monitoring suspected criminals' communications by bugging telephones, apartments or cars, the police collect information for ongoing investigations and the later proceedings in court. If foreign-language-speaking suspects are involved, intercept interpreters are indispensable for police work. Intercept interpreting is a hybrid translational activity that encompasses elements of interpreting and translation. This article explores the competences and skills required for this activity. It is based on 24 semi-structured interviews with intercept interpreters and police officers and on an observational study conducted in a Swiss police department. Core elements of translation and interpreting competence models are combined to reflect the hybrid nature of the activity. In a qualitative data analysis, we deductively identified typical translation and interpreting sub-competences, while a concurrent inductive analysis allowed us to extend the competence framework by new, specific elements of intercept interpreting. The results show that intercept interpreters not only exhibit special investigative and forensic skills, but that they also have many mental and emotional skills that enable them to carry out their demanding activity.